Sistematik Literatur Review: Peran Sistem Kesehatan dalam Penurunan Angka Kematian Ibu dan Anak - Purba, Sri Hajijah; Ariyani, Irgi; Delima, Delima; Nasution, Muhammad Shofwan Rusdy (Lembaga Yasin AlSys, 2025)
The maternal and child mortality rate (AKI-AKB) is an important indicator in determining the level of welfare of a country. A resilient health system plays an important role in reducing AKI-AKB. Such as the provision of universal access to essential health services, training of medical personnel focused on maternal and child health, and technology-based data management have been proven to support the reduction of these numbers in various countries. This research uses a qualitative method that is a literature study, namely a study that uses books and other literature as the main object. The data collection technique was carried out by examining literature sources from academic databases such as Google Scholar, ScienceDirect, Indonesian journal portals, and academic reference books. The results of the study show that the results of the maternal mortality rate (AKI) and infant mortality rate (AKB) in Indonesia in 2022 and 2023. In 2022, the maternal mortality rate was recorded at 4,005 people, while the infant mortality rate reached 20,882 people. However, in 2023, the maternal mortality rate increased to 4,129 people, and the infant mortality rate also increased significantly to 29,945 people. This increase shows a major challenge in Indonesia's health system, despite the fact that various programs have been implemented to reduce maternal and child mortality. In conclusion, government programs, such as family planning, reproductive health services, emergency obstetric services, and postpartum care, demonstrate strategic efforts in preventing complications and reducing maternal and infant mortality. With an integrated and sustainable approach, this effort is expected to be able to significantly reduce AKI and AKB.